أهمية سيطرة البحرية الجزائرية على الحوض المتوسط ودورها في تحرير مدينة وهران من الأسبان (1792م) - العايدي, رشيد (جامعة الوادي - University of Eloued, 2022)
(The strategic importance of the city of Oran made the Spaniards occupy it in 1509 AD, to be liberated in 1708 AD during the reign of the Dey Mohamed Bakdash, but this did not prevent them from occupying it again, beginning in the year 1732 AD, to be liberated from the Spaniards for good in 1792 AD, after Maratonic wars through which they were able The Algerian navy is to return the measure to the Spaniards, forcing them to conclude a treaty that they have signed humbly, This is after the Algerian control over the Mediterranean basin and its domination of the entire region after the increase in the strength of its naval fleet and the skill of its leaders, which enabled it to liberate the gaps from which it was robbed, to stand in this way as a wall against any harassment or possible maneuvers from hostile countries to control any region of Algeria, but it With the crash of its fleet in the Battle of Navarreen, it lost control of the Mediterranean basin, which made the European countries harass it, like France, which lost it one fortress after another and one castle after another to fall under occupation despite the stubbornness of its army and people in responding to this aggression.
مقال
Keywords: الحوض المتوسط,البحرية الجزائرية,وهران,إسبان; middle basin; Algerian Navy; Oran; Spaniards; Release